2007
DOI: 10.1172/jci28281
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lymphocytic leukemia requires BCL2 to sequester prodeath BIM, explaining sensitivity to BCL2 antagonist ABT-737

Abstract: Antiapoptotic B cell leukemia/lymphoma 2 (BCL2) family proteins are expressed in many cancers, but the circumstances under which these proteins are necessary for tumor maintenance are poorly understood. We exploited a novel functional assay that uses BCL2 homology domain 3 (BH3) peptides to predict dependence on antiapoptotic proteins, a strategy we call BH3 profiling. BH3 profiling accurately predicts sensitivity to BCL2 antagonist ABT-737 in primary chronic lymphocytic leukemia (CLL) cells. BH3 profiling als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

35
540
2
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(583 citation statements)
references
References 40 publications
35
540
2
6
Order By: Relevance
“…CLL cells depend on BCL-2 for survival and can be considered BCL-2-addicted. 27,28 Both ABT-263 and ABT-199 induced a rapid concentration-dependent apoptosis in primary CLL cells, which was evident both at early times (4 h) and at low nanomolar concentrations in agreement with previous studies. 10,29 The only other inhibitor to induce a similar rapid concentration-dependent induction of apoptosis in primary CLL cells was UCB-1350883, although it was much less potent than either ABT-263 or ABT-199 (Figure 4b).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…CLL cells depend on BCL-2 for survival and can be considered BCL-2-addicted. 27,28 Both ABT-263 and ABT-199 induced a rapid concentration-dependent apoptosis in primary CLL cells, which was evident both at early times (4 h) and at low nanomolar concentrations in agreement with previous studies. 10,29 The only other inhibitor to induce a similar rapid concentration-dependent induction of apoptosis in primary CLL cells was UCB-1350883, although it was much less potent than either ABT-263 or ABT-199 (Figure 4b).…”
Section: Resultssupporting
confidence: 91%
“…27,28 However, a dose-limiting thrombocytopenia is observed owing to inhibition of BCL-X L , the primary survival factor for platelet viability. 33 This has resulted in the synthesis of ABT-199, a BCL-2-specific inhibitor, which appears to act in vivo to specifically inhibit BCL-2 without affecting BCL-X L , and thus platelets are spared.…”
Section: Discussionmentioning
confidence: 99%
“…5 It potently inhibits the BH3-binding activity of Bcl-2, Bcl-xL and Bcl-w but not that of Mcl-1 and Bfl-1. 9 ABT-737 promotes cell death by displacing, from its targets, 'BH3 activators' such as Bim or Puma (BH3-only proteins that can directly activate multi-domain proteins when free from anti-apoptotic proteins) 10,11 and/or active Bax. 12 Efficient induction of apoptosis by ABT-737 requires that proapoptotic proteins are not sequestered by an excess of empty Mcl-1 or Bfl-1 that are not efficiently inhibited by ABT-737.…”
mentioning
confidence: 99%
“…ABT-737 displaces proapoptotic BH3-only from Bcl-2 or Bcl-xL, leading to activation of Bax and Bak and downstream caspases (9). Because of the low affinity of ABT-737 for Mcl-1, high basal levels of Mcl-1 have been associated with ABT-737 resistance (11)(12)(13)(14). Previous studies have also shown that ABT-737 is effective as a single agent against some leukemia/ lymphoma cell lines both in vitro and in vivo (11,(15)(16)(17).…”
mentioning
confidence: 99%